A Comparison of In-Vivo and Videoconference Momentary Time Sampling Observations of On-Task Behavior. (December 2019) - Fischer, Aaron J.; Dart, Evan H.; Lehman, Erica; Polakoff, Ben; Wright, Sarah J.
Systematic direct observation (SDO) is frequently used in schools to document student response to evidence-based interventions, determine eligibility for special education services, and provide objective data during high-stakes decisions. However, there are several limitations associated with this widely used data collection tool including a shortage of service providers available to implement it and the significant travel time required for itinerant personnel. Using videoconferencing (VC) software to aid in the implementation of SDO is an intuitive application of technology that stands to increase the feasibility and efficiency with which SDO can be utilized in research and practice. The purpose of this study was to evaluate the reliability and equivalence of the results generated from two modes of SDO, traditional in-vivo SDO and SDO conducted through VC software. The results suggest that VC SDO produces estimates of student on-task behavior that are practically equivalent (i.e., ±3%) to estimates generated through traditional SDO. Furthermore, two frequently used reliability indices indicate that VC SDO results are adequately reliable against traditional in-vivo SDO. Implications for school-based practice are discussed.